Lady Audley's secret - Braddon, M. E. (Mary Elizabeth), 1835-1915 (Oxford world's classics., 2008)
A barrister becomes a detective when his friend disappears at an English manor in this classic Victorian novel. Beautiful Lucy Graham charms every man she meets, including wealthy widower Sir Michael Audley. After they marry, he refurbishes his mansion to create a little palace for his new wife, where her future seems bright. Her past, however, is shrouded in darkness, and she'll do whatever it takes to keep it hidden. Then Sir Michael's nephew, Robert, a London barrister, comes for a visit with his good friend George Talboys for a week of fishing. But when George mysteriously vanishes, there's no time to relax. Increasingly suspicious of his new aunt, Robert searches for clues, determined to find his friend and discover exactly who Lady Audley really is. One of the most popular examples of the "sensation novel" craze that swept England during the nineteenth century, Lady Audley's Secret is said to reflect themes from a real-life crime of the era, the notorious Constance Kent case